Diversity for well-being: Making the most of agricultural biodiversity: IPGRI's new strategic directions - International Plant Genetic Resources Institute (2004)
IPGRI, in consultation with its partners and stakeholders, has drawn up a new strategy to guide its operations over the coming years. It sets out the ways in which IPGRI will contribute to the overall goal of helping society at large to meet the Millennium Development Goals.